Unlocking Sales Insight through Business Intelligence and ERP - Aulia, Azka; Desanti, Ririn Ikana; Amri, Mahfudz (ULTIMA InfoSys, 2025)
In recent years, companies have experienced growing competition, financial inefficiencies, and operational instability, which have contributed to declining profitability. Digital transformation is found to increase operational efficiency while minimizing risk of insolvency. PT Dwi Family Investama, an offset and printing company, experiences similar problems from its manual record of orders and invoices, which causes decreased efficiency, errors, and complicated handling of customer information. Such inefficiencies slow down business strategy formulation and decision-making. This research designs a web-based Enterprise Resource Planning (ERP) system integrated with business intelligence dashboard to facilitate better decision-making. The system automates business processes and delivers real-time operational insights through an interactive dashboard. Performance assessments record an increase in operational efficiency by 52.3%, proving the system’s effectiveness in improving business operations and decision-making.